2017
DOI: 10.3389/fimmu.2017.00832
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen (HLA) and Immune Regulation: How Do Classical and Non-Classical HLA Alleles Modulate Immune Response to Human Immunodeficiency Virus and Hepatitis C Virus Infections?

Abstract: The genetic factors associated with susceptibility or resistance to viral infections are likely to involve a sophisticated array of immune response. These genetic elements may modulate other biological factors that account for significant influence on the gene expression and/or protein function in the host. Among them, the role of the major histocompatibility complex in viral pathogenesis in particular human immunodeficiency virus (HIV) and hepatitis C virus (HCV), is very well documented. We, recently, added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 356 publications
(444 reference statements)
5
125
3
1
Order By: Relevance
“…Severe diarrhoea is a cause of systemic inflammation and may also lead to ischemic injury to grafts because of dehydration or volume depletion . Recently, growing evidence has indicated that production of DSA is attributable to increased alloreactivity by multiple types of infections, including Cytomegalovirus . In the present study, the infectious and non‐infectious diarrhoea groups showed an elevated risk of DSA, despite different classes of DSA and the dependence on the change in immunosuppressive regimen.…”
Section: Discussionmentioning
confidence: 48%
“…Severe diarrhoea is a cause of systemic inflammation and may also lead to ischemic injury to grafts because of dehydration or volume depletion . Recently, growing evidence has indicated that production of DSA is attributable to increased alloreactivity by multiple types of infections, including Cytomegalovirus . In the present study, the infectious and non‐infectious diarrhoea groups showed an elevated risk of DSA, despite different classes of DSA and the dependence on the change in immunosuppressive regimen.…”
Section: Discussionmentioning
confidence: 48%
“…HLA‐II genes have a substantial role in the formation of HIV CD4+ T cell syncytia. However, the HIV‐infected subjects fail to present an immune response to this region …”
Section: Discussionmentioning
confidence: 99%
“…HLA-II genes have a substantial role in the formation of HIV CD4+ T cell syncytia. However, the HIV-infected subjects fail to present an immune response to this region 30. Tumor necrosis factor (TNF), as a proinflammatory cytokine, has several functions in different diseases including cell differentiation, necrosis, proliferation, and apoptosis.…”
mentioning
confidence: 99%
“…138 Now, antibody-binding sites in a given HLA (MHC) molecule are mostly prediction-servers predetermined on the basis of particular binding motifs and the anchor residues. 139,140 These residues refer to known amino acids located at defined locations in the peptide chain and which are peculiar to each MHC molecule. 141,142 Prediction-server database of peptide motifs and/or of MHC ligands may be obtained from web-based and/or from prediction-servers dedicated to NetMHC family.…”
Section: The Subpopulation Levelmentioning
confidence: 99%